Control of selected fermentation indices by statistically designed experiments in industrial scale beer fermentation - Krzysztof Kucharczyk; Krzysztof Żyła; Tadeusz Tuszyński (Czech Journal of Food Sciences, 2020)
Fermentation indices of a bottom-fermented lager brew from high gravity wort (15.5 °P) were analysed using the response surface methodology (RSM, Box-Behnken design). Fermentation parameters like pitching rates (6-10 mln cells mL-1), wort aeration (8-12 mg O2 mL-1), different times (4.5-13.5 h) of filling CCTs (cylindroconical fermentation tanks; 3 850 hL) and fermentation temperatures (8.5-11.5 °C) were modulated to assess their impact on the fermentation indices. Within the studied ranges of fermentation parameters the experimental factors had a significant influence (R2 for the model 73%) on alcohol content, pH (83%), extract drop (86%), FAN consumption (70%), bitterness loss (73%) and sensory analysis (71%). Based on the multiple response optimisation analysis, the values of independent factors that optimised alcohol content at the level of 6.94% (v/v), extract drop at 1.77 °P per day with maximization of FAN consumption (ca. 128 mg L-1) and pH drop to the level of 4.69 with minimized bitter substances losses (6.2 BU) were as follows: pitching rate 6 mln cells mL-1; fermentation temperature 11.2 °C; aeration level 10.5 mg L-1; and CCTs filling time 13.5 h.